2021
DOI: 10.30880/ijie.2021.13.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Lightweight Composite Slab System

Abstract: This study investigate the structural behavior of lightweight composite slab system that consist of profiled steel sheet (PSS) attached to dry board (DB) using mechanical screws and with or without infill materials. A total four full-scale panel specimen were tested under four-point bending when subjected under static loading. Result of the four-point test shows that increasing the thickness of profiles steel sheet gives major effect to the deflection and ultimate load. The deflection and ultimate load of 1.0m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The lightweight composite slabs were examined to obtain the failure mechanism under full load capacity. In another study by Sutiman et al [27], foamed concrete was used as the infill material for the lightweight composite slabs, which consist of Primaflex dry board and PEVA 50. It was found that foamed concrete has a minor impact on serviceability.…”
Section: Lightweight Composite Slabsmentioning
confidence: 99%
“…The lightweight composite slabs were examined to obtain the failure mechanism under full load capacity. In another study by Sutiman et al [27], foamed concrete was used as the infill material for the lightweight composite slabs, which consist of Primaflex dry board and PEVA 50. It was found that foamed concrete has a minor impact on serviceability.…”
Section: Lightweight Composite Slabsmentioning
confidence: 99%
“…Jaini et al [21] fabricated cemboardfoamed concrete panel using PRIMAflex. Similarly, Sutiman et al [22] used PRIMAflex to prepare specimens for the lightweight steel composite slab.…”
Section: Primaflexmentioning
confidence: 99%
“…Even with these limitations, a higher volume of studies focusses on the development of steel-concrete infill systems [14], owing to the increase in compressive strength and increased panel stiffness delaying the buckling offered by these composite slabs [15]. Moreover, the profile sheeting provides support by acting as a formwork taking the selfweight of concrete under large spans, avoiding the need for temporary props [16,17]. However, some studies identify that using conventional concrete as an infill material would negatively affect the sustainability aspect of the modular construction concept due to the high amount of carbon emissions associated with the production of Ordinary Portland Cement [18].…”
Section: Introductionmentioning
confidence: 99%